2003
DOI: 10.1002/sia.1489
|View full text |Cite
|
Sign up to set email alerts
|

Formation of promising Co–C nanocompositions

Abstract: Encapsulation of Co nanoparticles ∼20 nm in size by C 60 -based substances has been realized by simultaneous deposition of cobalt (electron beam evaporation) and C 60 fullerene (thermal sublimation) on (0001) a-Al 2 O 3 and (001) NaCl substrates at room temperature under 10 −5 Pa. Sharp hills 20 nm above the film surface were detected by atomic force microscopy and scanning electron microscopy. Electron diffraction analysis revealed the existence of diamond near distorted fcc Co crystals. Graphite, Co 2 C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In order to combine aTM with C 60 , themethod of simultaneous deposition is applied [5,[16][17][18][19]. This method has beenfound to be effective for the formation ofTM-C 60 compounds [16,19], despite thefact that its application frequently results in the formation of composite nanostructures due to easy TM clustering in the deposited TM-C 60 mixture films [5,[16][17][18][19][20][21][22]. In spite of the difficulties in thecreation ofTM-C 60 fullerides,simultaneous deposition provides attractive composite nanostructures, suggesting interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to combine aTM with C 60 , themethod of simultaneous deposition is applied [5,[16][17][18][19]. This method has beenfound to be effective for the formation ofTM-C 60 compounds [16,19], despite thefact that its application frequently results in the formation of composite nanostructures due to easy TM clustering in the deposited TM-C 60 mixture films [5,[16][17][18][19][20][21][22]. In spite of the difficulties in thecreation ofTM-C 60 fullerides,simultaneous deposition provides attractive composite nanostructures, suggesting interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…Their cytotoxicity [5,6] has thus become a crucial problem for further development in vivo, and many solutions have been suggested, including coating nanoparticles with carbon, silica and organics [7][8][9][10][11][12][13]. But our recent results [14] indicated that core/shell structure metallic nanoparticles (Fe, Co, Ni) were still rendered slightly cytotoxic due to the incomplete integrity Carbonization [17], CVD [18,25], chemical reaction [19][20][21]26], self-assembly [22], simultaneous deposition [24] Orthorhombic Monolithic [17][18][19][20]/mixture [17][18][19][20][21][22][24][25][26] Co 3 C CVD [18,25], chemical reaction [19,20,26], arc discharge [23], simultaneous deposition [24] Orthorhombic Mixture [18][19][20][22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Being this shift in the IR bands irreversible, it is ascribed to cobalt surface reconstruction from an fcc structure to a more open crystallographic structure, the last one behaving as the true active site under working conditions [65]. Notice the parallel appearance of an IR band at 642 cm À1 ascribed to cobalt-carbon species [70,71] which provides the first experimental evidence for the role of carbon atoms in promoting surface reconstruction of the cobalt particle under FT conditions, in agreement to previous DFT calculations [72].…”
Section: Nature Of Active Sites In the Fischer-tropsch Reactionmentioning
confidence: 99%